How do Chinese marine firms embed in global value chains? Peer effects perspective - Tian, Weijian; Zhao, Yingqin (Frontiers in Marine Science, 2025)
IntroductionThis study investigates how Chinese marine firms are motivated to embed in the global value chains from the perspective of peer effects. The motivation mechanism is examined and tested from three perspectives: learning motivation, competitive motivation and information motivation.MethodsThe marine companies that were listed between 2008 and 2016 on the Shanghai and Shenzhen A-shares serve as our samples. A number of robustness tests support the study’s conclusion.ResultsChinese marine companies’ embed in the global value chains has industry peer effects. According to the mechanism analysis, the leader firms in marine enterprises embed in the GVCs peer effects for “competitive motivation” and “information motivation”, while the following companies do the same for “learning motivation” and “information motivation.” According to heterogeneity analysis, peer effects are particularly prominent in places with state-owned marine firms, high proportion of FDI and high degree of marketization.DiscussionThe driving forces behind marine firms’ embed in global value chains are explored in this study, which also offers managers of marine enterprises decision-making resources.